NEW SPECIES OF CONIFER DEFOLIATORS IN COLOMBIA - MADRIGAL-C., ALEJANDRO (Revista Colombiana de Entomología, 1981)
Reforestation with different species of conifers, especially cypress (Cupressus lusitanica Mili. and C. sempervirens L.) and pine (Pinus patula Schl.) has been intensified during the last years but has been limited by the attack of lepidopterous defoliators, of which the best known are Glena bisulca Rindge and Oxydia trychiata (Guenée) (Geometridae). This study presents preliminary information on the biology, habits, distribution in the country, and damage caused by four new geometrid species: "chapola parda", Bassania schreiteri Schaus; "chapola Blanca", genus Cargolia or near; "Gusano rugoso", Neodesmodes arana Dognin; and the "green measuring worm", Melanophia commotaria (Maassen). The first three species have been found attacking cypress and pine in different localities of Antioquia, Risaralda, and Caldas. The fourth one is only present in Antioquia and Caldas.